Survival, self-sufficiency, and repair: reentry strategies and resources for wrongfully convicted people - Nowotny, Jordan (Psychology, crime & law, 2022)
In this paper we draw on 26 in-depth interviews to explore the strategies and resources utilized by wrongfully convicted people to transition from prison to communities. Our findings suggest a multi-layered approach is necessary to address the challenges of reentry and reintegration for this sample. For some wrongfully convicted people, their adjustment to the community was affected by their experiences while incarcerated. Those who had more resources in prison were able to develop advantages making post-release hurdles more manageable. In the period directly after release, instrumental needs were critically important and typically supported by family members, friends and/or innocence organizations. Following this period, exonerees worked towards achieving sustainable routines, which usually involved obtaining employment to become financially secure. Many exonerees actively sought out opportunities to repair damages done through either mental health professionals or other exonerees/innocence support agencies; however, this process rarely resulted in feelings of closure. Nevertheless, many of the people interviewed in this project were successful after release but sometimes required services and support networks to build meaningful, healthy lives after prison. Study limitations and other policy implications are also discussed.